Post Occupancy Evaluation of postgraduate students’ hostel facilities and services - Agyekum, K.; Ayarkwa, J.; Amoah, P. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Construction Post Occupancy Evaluation studies, especially those related to students’ hostels has received worldwide attention. However, this has not been the case in Ghana. This study sought to evaluate the performance of two postgraduate hostel buildings (Steven Paris Hostel and Transport Hostel) on Kwame Nkrumah University of Science and Technology (KNUST) campus with regards to services rendered by management, functionality and environmental friendliness. The objective was to investigate the level of students’ satisfaction with some selected facilities and services available at the hostels. A survey of 70 postgraduate students who were residents of the two hostels were conducted to achieve the objective of the study. Data obtained from the survey was analyzed by Relative Satisfaction Index (RSI) and mean aggregate RSIs. The findings from the study revealed that occupants are generally “Satisfied” (Mean Aggregate RSI of 68.05) with the facilities and services available at the postgraduate hostels. The occupants showed high satisfaction level with the bedroom, television room, bathroom, kitchen, meeting room, support services and lobbies. However, they were indecisive about their satisfaction with management of the hostels and the laundry room. The feedbacks obtained from the occupants should inform any decisions regarding future renovations and effective management of the hostels. The study recommends effective POEs and maintenance management practices for the institution’s hostel facilities to improve the comfort of users.